(untitled) (Journal of Social Sciences Review, 2022)
In Pakistan, 0.543 million children have been placed in residential care facilities. This study has been carried out to explore whether or not the orphans in the orphanages of Khyber Pakhtunkhwa have been provided with enough nutritious food. For this purpose, four orphanages, i.e. Peshawar, Kohat, Abbottabad, and Swat, were selected from five zones in KP. The Child Status Index was used to collect rich data from the participants and was then analyzed by using SPSS (V.22). It was found that a significant majority of the orphans were being provided with good food and found to be well fed and eating regularly. Similarly, it was also found that the majority of the participants were well-grown and had good height and energy levels. The one-way ANOVA shows that there was no significant difference between food security and nutrition and growth. In light of Bowlby’s (1951) theory of attachment, it was found that due to deprivation from an attachment figure, i.e. their mothers and primary caregivers, some orphaned children were found to be stunted and underweight. It is recommended that orphaned children should be placed into orphanages for a minimum period of time; however, such placement shall be the last resort.